Self Harm Behavior in Female Boarding School Students: Overview of Social Anxiety and Self Esteem - Khasanah, Sa'idatul; Raharjo, Trubus (Hikmah, 2024)
Self harm behavior in female santri in pesantren can be influenced by social anxiety and low self esteem. This study aims to analyze the relationship between social anxiety and self esteem with self harm behavior in female students at pesantren. The major hypothesis test showed a significance level value of p of 0.000 (p < 0.01) with Rx1,2y = 0.701 there is a very significant relationship between social anxiety and self esteem with self harm so that the hypothesis stating there is a relationship between social anxiety and self esteem with self harm behavior in female students in pesantren is accepted, with an effective contribution of 49.2%. The results of the minor hypothesis test between the variables of social anxiety and self harm showed a correlation coefficient between the two variables (Rx1y) of 0.689 with a p value of 0.000 (p < 0.01). The results show that there is a positive relationship between social anxiety and self harm with an effective contribution of social anxiety and self harm of 47.5%. The results of the minor hypothesis test between the variables of self esteem and self harm showed a correlation coefficient between the two variables (Rx2y) of -0.554 with a p value of 0.000 (p < 0.01). The results show that there is a negative relationship between self esteem and self harm with an effective contribution of self esteem and self harm of 30.7%.